Financing options for loss and damage: a review and roadmap - J. Timmons Roberts; Saleemul Huq; Alexis Durand; Victoria Hoffmeister; Jonathan Gewirtzman; Sujay Natson; Romain Weikmans (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Pressure to support responses to loss and damage under the United Nations Framework Convention on Climate Change (UNFCCC) has intensified in recent years. Loss and damage – an issue gaining prominence largely due to shortfalls of mitigation action and adaptation support – has never been officially defined under the UNFCCC. Here, the term “loss and damage” refers to irreversible losses (e.g. loss of life, species, land) and costly damages (e.g. destroyed infrastructure) caused, at least in part, by climate change. Although loss and damage has been a subject of debate among Parties to the UNFCCC for years, the agreement reached in Paris was the first to devote a full article to loss and damage. In that article, Parties agreed to enhance “understanding, action and support” for loss and damage and to strengthen the Warsaw International Mechanism for Loss and Damage associated with Climate Change (WIM) (UNFCCC, 2015, Art. 8). In coming years, as climate change advances and Parties work to implement this and other directions from the Paris Agreement, it will prove more crucial than ever to support loss and damage response, especially should efforts to sufficiently scale up mitigation commitments and adaptation capacity fall short. Given mounting pressure to finance effective loss and damage response efforts, understanding of the Warsaw International Mechanism's activities must be strengthened, and the question of how funding for loss and damage response might be raised and allocated must be widely considered. To these ends, this paper endeavours to answer two questions at the core of the emergent drive to fund efforts to address loss and damage. First, what do we mean by financing loss and damage response? We examine language relevant to financing efforts in the initial two-year workplan of the Executive Committee (ExCom) of the WIM to answer this question, reviewing the workplan's listed financing options (see Table 1 in Section 2.7 for a summary). Second, what are some possible means for raising predictable funding that will prove adequate to finance loss and damage response? We discuss a number of innovative fundraising mechanisms that have been proposed and assess their adequacy, predictability, technical feasibility, fairness (whether polluters or the most vulnerable pay), indirect effects and link to loss and damage (see Table 2 in Section 3.7 for a summary). These criteria provide a framework to evaluate the concepts that underlie each mechanism (such as fairness and links to loss and damage), to assess whether each mechanism can be implemented and become a sufficient, stable source of support for loss and damage response (using criteria of feasibility, adequacy and predictability), and to judge what tangential impacts use of each mechanism might produce (by examining potential indirect effects). We conclude that there are a number of viable proposals for both gathering and effectively using funds to support loss and damage response. Two proposals stand out: a levy on airline travel and risk transfer approaches. However, we also identify a number of outstanding issues in funding loss and damage response, including the ambiguity of relevant UNFCCC texts; the shortfalls of proposed mechanisms in terms of providing for slow onset or high-certainty events and non-economic loss and damage; the lack of an agreed definition of loss and damage under the UNFCCC; developed countries' disproportionate (and inadequate) support for risk transfer over other approaches; the large gap that exists between funding made available and funding needed; and the inevitable contention surrounding the question of how finance should be distributed.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Klimawandel